Pregnancy-associated mortality in Taiwan, 2004-2011 - Li Sha; Tung-Pi Wu; Fu-Wen Liang; Lea-Hua Chen; Tsung-Hsueh Lu; Ya-Li Huang (Elsevier, 2016)
Objective: Pregnancy-associated death is defined by the American College of Obstetricians and Gynecologists as "a death of a woman while pregnant or within 1 year of termination of pregnancy, irrespective of the cause of death." We sought to determine pregnancy-associated mortality ratio (PAMR) in Taiwan and to compare the cause of death pattern with other countries to assess the national health status of Taiwanese women. Materials and methods: We linked four nationwide population-based data sets (birth registration, birth notification, National Health Insurance claims, and cause of death mortality) from 2004 to 2011 to identify women aged 15-49 years that died from pregnancy-associated deaths. We then calculated the PAMR and cause of death distribution by maternal age. Results: A total of 559 pregnancy-associated deaths were identified with an overall PAMR of 36 (deaths per 100,000 live births). The J-shaped age-specific PAMR mortality pattern was noted, in which the PAMR was 32, 25, 24, 36, 71, 143, and 369 for women aged 15-19 years, 20-24 years, 25-29 years, 30-34 years, 35-39 years, 40-44 years, and 45-49 years, respectively. The age-standardized PAMR decreased drastically from 45 in 2004-2005 to 36 in 2006-2007 and 30 in 2008-2009, but leveled off to 33 in 2010-2011. The proportion of indirect causes increased from 2004-2007 to 2008-2011 among women aged 15-29 years and 35-49 years. Conclusion: Compared with previous studies, the PAMR of Taiwan is moderate. However, the proportion of external causes of pregnancy-associated deaths in Taiwan is the lowest compared with other regions. Further studies (such as death review) are needed to explore possible preventable factors.